Looking at Covid-19 vaccine hesitancy through a macro perspective. A comparative study of Italy, Poland and Portugal - Cervia, Silvia; Sawicka, Maja; Sena, Barbara; Serapioni, Mauro (PARTECIPAZIONE E CONFLITTO, 2023)
This article aims to overcome the most common interpretive paradigms on vaccine hesitancy and refusal when are limited to consider the individual or group level and provide a contextual reading. For the purpose of this study, cultural, economic and political conditions are considered constituent materials of "thinking" and "doing" in everyday life and of "problematizing" the issue of vaccines in the Covid-19 era. By adopting an analytical model derived from Sewell's pattern of contextualized structures (as a result of schemas and resources), the article compares three exemplary cases: Portugal, the country with the highest rate of Covid-19 vaccination; Italy, one of the most vaccine-hesitant western countries in Europe; and Poland, which with its vaccination rate well exemplifies vaccine-hesitant post-socialist CEE countries. By combining the schemas and resources, this study gives a social map with types of context-driven structures and offers an initial interpretative key useful to understanding the complexity of problem framing and structuring in the Covid-19 pandemic era in different sociocultural and political contexts.